A influência dos impostos na demanda por carros no Brasil: otimização da arrecadação com base na Curva de Laffer - Almeida, Matheus de Oliveira (2025)
This study analyzes the influence of taxes on car demand in Brazil. Objective: To assess whether the tax policy applied to the automotive sector has been effective in maximizing fiscal revenue while preserving demand. Materials and Methods: An empirical approach is employed, grounded in microeconomic and econometric tools, using data from the period 2002 to 2022. Results: The findings show that increases in the tax burden significantly reduce vehicle sales, and that the tax rates applied during the analyzed period were above the level capable of maximizing revenue, pointing to a revenue shortfall. The model demonstrated good explanatory power and statistical validity, with evidence of cointegration among the variables. Discussion: There is room to improve the sector’s tax policy, aiming for greater efficiency without compromising the population’s access to car consumption, while respecting practical constraints and the multiple objectives involved